A Fraction Has To Be Made

Calculus Level 3

We know that the limit of ratios of the two functions x 2 + x + 1 \sqrt{x^2+x+1} and x 2 x 1 \sqrt{x^2-x-1} as x x approaches infinity is equal to 1. That is,

lim x x 2 + x + 1 x 2 x 1 = lim x 1 + 1 / x + 1 / x 2 1 1 / x 1 / x 2 = 1. \displaystyle \lim_{x\to\infty} \dfrac{ \sqrt{x^2+x+1} }{\sqrt{x^2-x-1}} = \lim_{x\to\infty} \sqrt{ \dfrac{1 + 1/x + 1/x^2}{1 - 1/x - 1/x^2} } = 1 .

Is it also true that the limit of the differences of the two same functions as x x approaches infinity is also equal to 1? That is, is the following limit true?

lim x ( x 2 + x + 1 x 2 x 1 ) = 1 \displaystyle \lim_{x\to\infty} \left ({ \sqrt{x^2+x+1} } - {\sqrt{x^2-x-1}} \right) = 1

Yes, it is true No, it is not true

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Relevant wiki: Limits by Rationalization

Rationalising we get , S = lim x 2 ( x + 1 ) x 2 + x + 1 + x 2 x 1 \displaystyle S=\lim_{x\to \infty} \frac{2(x+1)}{\sqrt{x^2+x+1}+\sqrt{x^2-x-1}}

So dividing by x x up and down we get , S = lim x 2 ( 1 + 1 x ) 1 + 1 x + 1 x 2 + 1 1 x 1 x 2 = 2 2 = 1 \displaystyle S=\lim_{x\to\infty} \frac{2(1+\frac{1}{x})}{\sqrt{1+\frac{1}{x}+\frac{1}{x^2}}+\sqrt{1-\frac{1}{x}-\frac{1}{x^2}}} = \frac{2}{2}=1

Great! This is the easiest technique to solve this problem.

Challenge Master Note: Can you think of another technique?

Pi Han Goh - 4 years, 11 months ago

Log in to reply

factor out x 2 , x^2 , we get

L = lim x x ( [ 1 + ( 1 x + 1 x 2 ) ] 1 2 [ 1 + ( 1 x 1 x 2 ) ] 1 2 ) \quad L = \displaystyle \lim_{ x \to \infty} x\left( \left[ 1+\left( \dfrac{1}{x}+\dfrac{1}{x^2} \right) \right]^{\frac12}- \left[1+\left(-\dfrac{1}{x}-\dfrac{1}{x^2} \right) \right]^{\frac12}\right)

Use binomial expansion: L = lim x x ( 1 + 1 2 ( 1 x + 1 x 2 ) + 1 1 2 ( 1 x 1 x 2 ) ) L = lim x x ( 1 x + 1 x 2 + ) = 1 L = \displaystyle \lim_{ x \to \infty} x \left( 1+\dfrac12\cdot\left( \dfrac{1}{x}+\dfrac{1}{x^2} \right)+\cdots-1-\dfrac{1}{2}\cdot\left(-\dfrac{1}{x}-\dfrac{1}{x^2} \right)-\cdots \right) \\ L =\displaystyle \lim_{ x \to \infty} x\left(\dfrac1{x}+\dfrac{1}{x^2}+\cdots \right) = \boxed{1}

Sabhrant Sachan - 4 years, 11 months ago

Stolz-Cesaro theorem is another way to do this

Aditya Narayan Sharma - 4 years, 11 months ago

@Pi Han Goh This problem is useless, and this solution is useless because there are too many people who dont know the limit functions well in the world, and I belong to the people I said.

. . - 3 months, 1 week ago

Log in to reply

So you want me to enable your request because you don't know something and you don't want to learn about it?

Pi Han Goh - 3 months, 1 week ago
X X
Apr 9, 2018

lim x ( x 2 + x + 1 ( x + 0.5 ) ) = lim x ( ( x + 0.5 ) 2 + 0.75 ( x + 0.5 ) ) = lim x ( ( x + 0.5 ) ( x + 0.5 ) ) = 0 \displaystyle \lim_{x\to\infty} \left ({ \sqrt{x^2+x+1}-(x+0.5) } \right) = \lim_{x\to\infty} \left ({ \sqrt{ (x+0.5)^{2}+0.75}-(x+0.5) } \right) = \lim_{x\to\infty} \left ( (x+0.5)-(x+0.5) \right)=0 lim x ( x 2 x 1 ( x 0.5 ) ) = lim x ( ( x 0.5 ) 2 1.25 ( x 0.5 ) ) = lim x ( ( x 0.5 ) ( x 0.5 ) ) = 0 \displaystyle \lim_{x\to\infty} \left ({ \sqrt{x^2-x-1}-(x-0.5) } \right) = \lim_{x\to\infty} \left ({ \sqrt{ (x-0.5)^{2}-1.25}-(x-0.5) } \right) = \lim_{x\to\infty} \left ( (x-0.5)-(x-0.5) \right)=0 lim x ( x 2 + x + 1 x 2 x 1 ) = lim x ( [ x 2 + x + 1 ( x + 0.5 ) + ( x + 0.5 ) ] [ x 2 x 1 ( x 0.5 ) + ( x 0.5 ) ] ) = lim x ( ( x + 0.5 ) ( x 0.5 ) ) = 1 \displaystyle \lim_{x\to\infty} \left ({ \sqrt{x^2+x+1} } - {\sqrt{x^2-x-1}} \right) =\lim_{x\to\infty} \left ({ [\sqrt{x^2+x+1}-(x+0.5)+(x+0.5)] } - {[\sqrt{x^2-x-1}-(x-0.5)+(x-0.5)]} \right)= \lim_{x\to\infty} \left ( (x+0.5)-(x-0.5) \right)=1

Good attempt, but you just committed a fallacy.

lim x ( f ( x ) g ( x ) ) = ( lim x f ( x ) ) ( lim x g ( x ) ) \displaystyle \lim_{x\to\infty} ( f(x) - g(x)) = \left (\lim_{x\to\infty} f(x)\right ) - \left (\lim_{x\to\infty} g(x) \right) is only true if both lim x f ( x ) \displaystyle \lim_{x\to\infty} f(x) and lim x g ( x ) \displaystyle \lim_{x\to\infty} g(x) are finite.

Pi Han Goh - 3 years, 1 month ago

Log in to reply

I made a little correction to my solution.

X X - 3 years, 1 month ago

Log in to reply

Great! It's fixed!!! Thanksss +1

Pi Han Goh - 3 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...